Handbook of dairy foods and nutrition - Miller, Gregory D. (CRC Press, 2006)
The Importance of Milk and Milk Products in the Diet Nutrient Components of Milk and Milk Products Nutrient Contribution of Milk and Milk Products Recommendations to Include Milk and Milk Products in the Diet Protecting the Quality of Milk and Other Dairy Foods Kinds of Milk and Milk Products Dairy Foods and Cardiovascular Health Contribution of Milk and Milk Products to Fat, Saturated Fat, and Cholesterol Intake Dairy Nutrients, Dairy Foods, and Coronary Heart Disease Efficacy and Safety of Low-Fat, Low-Saturated Fat Diets Dairy Foods and Hypertension Dietary Patterns Including Dairy Foods and Blood Pressure Dairy Food Nutrients and Blood Pressure Other Lifestyle Modifications Comprehensive Lifestyle Modifications and Blood Pressure: Putting It All Together Dairy Foods and Cancer Dairy Foods, Calcium, Vitamin D, and Prevention of Colon Cancer Dairy Foods and Breast Cancer Dairy Foods and Prostate Cancer Dairy-Food Cultures and Cancer Other Protective Components in Dairy Foods Dairy Foods and Bone Health Bone Basics Risk Factors for Osteoporosis Calcium, Dairy Products and Bone Health Vitamin D and Bone Health Protein and Bone Health Additional Nutrients and Bone Health The Dairy Advantage Dairy Foods and Oral Health Dental Caries and Tooth Enamel Erosion Periodontal Disease Dairy Foods and a Healthy Weight Dairy Products and a Healthy Weight in Adults Experimental Animal Studies Potential Mechanisms Dairy Products and Weight/Body Composition in Children and Adolescents Lactose Digestion Physiology of Lactose Digestion Symptoms Diagnosis Relationship between Lactose Maldigestion, Intolerance, and Milk Intolerance Long-Term Consequences of Lactose Maldigestion Strategies for Dietary Management of Primary Lactose Maldigestion Treatment of.